2011
DOI: 10.1109/twc.2011.081611.102086
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Sidelobe Decaying Property of Walsh-Hadamard Code in MC-CDMA Systems

Abstract: In this letter, a spectral sidelobe-decaying property of the Walsh-Hadamard code employed in multicarrier codedivision multiple access (MC-CDMA) systems is exploited. It is shown that the sidelobe-decaying characteristic of the MC-CDMA signal can be properly described by the code index of the underlined Walsh-Hadamard codeword.Index Terms-Multicarrier code-division multiple access, spectral sidelobe, Walsh-Hadamard code, orthogonal frequencydivision multiplexing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It is showed that MC-CDMA can effectively combine all the energy of the received signal in the frequency domain. At the same time, a fast Walsh-Hadamard transform 17,18 can be made for spreading and dispreading in a single sub-channel to improve the computational efficiency of UASNs. Y Jiemin et al 19 propose an MC-CDMA scheme in design of UASNs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It is showed that MC-CDMA can effectively combine all the energy of the received signal in the frequency domain. At the same time, a fast Walsh-Hadamard transform 17,18 can be made for spreading and dispreading in a single sub-channel to improve the computational efficiency of UASNs. Y Jiemin et al 19 propose an MC-CDMA scheme in design of UASNs.…”
Section: Related Workmentioning
confidence: 99%
“…Finally, we conduct convex optimization according to equation (17). The convex optimization-based algorithm (COBA) mainly includes initialization, solving the semi-definite problem, implementing Cholesky decomposition, 47,48 and achieving convex optimization in four steps.…”
Section: Convex Optimization-based Mudmentioning
confidence: 99%
“…As opposed to the spreading of data in the time domain, as in the direct sequence CDMA technique, the spreading of data associated with the subcarriers in MC-CDMA is carried out in the frequency domain. In order to ensure orthogonality among users in the frequency domain, Walsh-Hadamard sequences are often implemented to achieve the spreading [4]. However, a disadvantage of the MC-CDMA system is that it is easily affected by imperfect channel frequency response estimation mismatch [5].…”
Section: Introductionmentioning
confidence: 99%